2019
DOI: 10.1007/s10452-019-09691-7
|View full text |Cite
|
Sign up to set email alerts
|

Feeding by two closely related species of Chironomus (Diptera: Chironomidae) in south Baltic lagoons, with implications for competitive interactions and resource partitioning

Abstract: Four major categories of food items were determined in the gut content of chironomid larvae collected in the Curonian and Vistula Lagoons in the spring-summer period of 2009-2011. These were detritus (range from 88 to 92% of the gut content, by volume), matter of plant (2-7%) and animal origin (0.2-0.5%), and mineral particles (3-7%). Plant matter comprised pine pollen, conidia of fungi, cyanobacteria, green algae and diatoms. Matter of animal origin consisted of remnants of oligochaetes and rotifers. Food con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
6
8
0
1
Order By: Relevance
“…But in our study, the data included gut content data other than detritus. As a result of our gut content study, Algae was the dominant component as in other studies (Tarkowska-Kukuryk 2013;Butakka et al 2016;Kornijo´w et al 2019). According to Kornijo´w et al (2019) food of animal origin is a less involved component than plant fragment as in our study.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…But in our study, the data included gut content data other than detritus. As a result of our gut content study, Algae was the dominant component as in other studies (Tarkowska-Kukuryk 2013;Butakka et al 2016;Kornijo´w et al 2019). According to Kornijo´w et al (2019) food of animal origin is a less involved component than plant fragment as in our study.…”
Section: Discussionsupporting
confidence: 75%
“…However, euglenoids were found only on the gut content of T. kraatzi (Figure 4). Several gut content studies reporting benthic algae as the basic food source for chironomids showed that diatoms especially constitute most of the diet (Tarkowska-Kukuryk 2013; Butakka et al 2016;Kornijo´w et al 2019). Members of the subfamily Chironominae, known as non-predatory fed primarily on algae especially diatoms, and in this study the algal diet of C. defectus, C. mancus and P. scalaenum (members of subfamily Chironominae) consisted of mostly diatoms (Figure 4).…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations